Kyrgyz Republic : Third Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Kyrgyz Republic has made good progress under the three-year Poverty Reduction Growth Facility arrangement. Executive Directors welcomed the strong macroeconomic performance and low inflation. They appreciated the fiscal consolidation by containing expenditure growth and improving tax collection. They welcomed the prudent monetary and strong exchange rate policies. They stressed the need to press ahead with privatization, restructure the power sector, and strengthen the financial system. They commended the successful completion of the third review under the Poverty Reduction and Growth Facility (PRGF) arrangement, and approved a waiver.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet